IMPACT OF LIQUIDITY, LEVERAGE, OPERATING CAPACITY, ON PROFITABILITY THROUGH FINANCIAL DISTRESS - Muhammad Yusuf; Tries Handriman Jamain; Findy Rachmandika Muhammad (Management and Sustainable Development Journal, 2024)
The purpose of the study is to determine the effect of Liquidity, Leverage, Operating Capacity, on Profitability through Financial Distress. This type of research is classified as survey research with theory development and hypothesis testing methods (explanatory). The results of the study show a significant effect of Liquidity on Financial Distress. Significant influence of Liquidity on Profitability. Significant influence of Leverage on Financial Distress. Significant influence of Leverage on Profitability. Significant influence of Financial Distress on Profitability. Significant influence of Operating Capacity on Profitability. Significant influence of Operating Capacity on Profitability.